ADESÃO AO PROTOCOLO DE IDENTIFICAÇÃO DO PACIENTE EM UNIDADES PEDIÁTRICAS: ESTRATÉGIA PARA O CUIDADO SEGURO - Panno, Simone Franciscatto (2017)
The correct identification of the patient is fundamental in the provision of safe care, being the first international safety goal of the World Health Organization. Protocols for patient identification in health services standardize actions and reduce the occurrence of errors. The general objective of this study was to evaluate the adherence of the professionals to the institutional protocol of identification of the patient, in the pediatric units of a teaching hospital. As specific objectives were considered: verify if the health care professionals identify the patients with bracelets; identification of the patient prior to care / procedures / transfers / discharge and educating / advising patients / caregivers on the correct identification, according to the protocol; verify the presence and general compliance of identification wristbands; and, produce a video emphasizing the importance of identification actions. A cross-sectional study was carried out, with a descriptive design and a quantitative approach. The population was composed by the health / support professionals, who worked in the care of patients of the Pediatric Emergency Room, the Pediatric Intensive Care Unit and the Pediatric Clinical and Surgical Unit of a teaching hospital in Rio Grande do Sul. The sample consisted of 385 opportunities of actions. At each opportunity, we sought: to verify if the patients were identified with bracelets - action 1; to observe if the professionals confer the identification of the patients - action 2; and, if the patients / companions were educated about the correct identification - action 3. Also, in the opportunities in which the bracelet was present, the conformity of the bracelet with the protocol was verified. Data collection took place from April to June 2017, through the completion of a research instrument. Data was entered into Excel 2007 spreadsheets and analyzed by descriptive statistics. The adhesion of professionals to action 1 was 74.28%, action 2 had no adhesion, and action 3 had adhesion of 2.08%. The bracelet was present at 82.85% of the opportunities and overall compliance was 12.22%. Regarding the location / fixation of the bracelet, compliance was 89.56%; in the presence of the three correct identifiers, 25.07% and, in the specifications, 69.29%. The findings contributed to establish the situational diagnosis of the professionals' adherence to the institutional protocol. In addition, it will enable the implementation of measures for compliance with the proposed actions and strengthening of the safety culture. The resulting product was a video aimed at informing and sensitizing health professionals / support, patients and caregivers as to the importance of the first goal.